6r-20=26+5r

Simple and best practice solution for 6r-20=26+5r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6r-20=26+5r equation:


Simplifying
6r + -20 = 26 + 5r

Reorder the terms:
-20 + 6r = 26 + 5r

Solving
-20 + 6r = 26 + 5r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-5r' to each side of the equation.
-20 + 6r + -5r = 26 + 5r + -5r

Combine like terms: 6r + -5r = 1r
-20 + 1r = 26 + 5r + -5r

Combine like terms: 5r + -5r = 0
-20 + 1r = 26 + 0
-20 + 1r = 26

Add '20' to each side of the equation.
-20 + 20 + 1r = 26 + 20

Combine like terms: -20 + 20 = 0
0 + 1r = 26 + 20
1r = 26 + 20

Combine like terms: 26 + 20 = 46
1r = 46

Divide each side by '1'.
r = 46

Simplifying
r = 46

See similar equations:

| -8x-24=40 | | 10+4x+6x=100 | | 8(3n+4)=8(8n+7)+2 | | b=2[36]/6 | | -2.5x=53 | | 56+12p=80+8p | | 8x+2=-64+2x | | 12+n=13 | | 5k-(3k-4)= | | 2x-4=14x+2 | | 4x+34=x+13 | | 56-12p=80-8p | | -39=5x-x-3 | | 15=m | | 2.5*5.4=x | | 17x+6=2(7x+4)+3x-2 | | n*(-2)=-11 | | -4x-4=0 | | 1+.6(q-4)=.4(q+1) | | 0.7x-4.7=0.9 | | 5m+2(mh)=23 | | 7-2r=15 | | 2x-7+3x=53 | | 3x+4x=x+6 | | .40x+.20(130)=.20(128) | | 7k-2=12 | | -3c-12=-5c+c | | 9J+3= | | 7y+3(y-6)=5(y+1)-2 | | 2x+5x=3x | | 4(6-3x)-8(X-24)=-7X+X | | 33+15x=3x-x+4x |

Equations solver categories